Natural soap is clinically effective and less toxic and more biodegradable in aquatic organisms and human skin cells than synthetic detergents - Takahide Kanyama; Akihiro Masunaga; Takayoshi Kawahara; Hayato Morita; Sadanori Akita (PLoS ONE, 2025)
In the era of COVID-19, concerns about and consumption of soaps and detergents have increased. The environmental effects, along with their direct impacts on the human body, are being simultaneously considered to ensure safety and support healthy living. Natural soap compounds are considered readily biodegradable and unlikely to produce hazardous waste, while artificial detergents are composed of synthetic surfactants, plasticizers, binders, and additives. This study aimed to investigate representative natural soap compounds consisting of fatty acid salts and compare them with synthetic detergents, such as sodium dodecylbenzene sulfonate (SDB) and sodium lauryl sulfate (SLS). Environmental assays recommended by the OECD, as well as human keratinocyte assays for toxicity and biodegradability, were utilized. The major components of natural soap were found to be less toxic and more biodegradable in aquatic environments—assessed using algae, crustaceans, and fish—compared to synthetic detergents. Additionally, in the human keratinocyte assay, natural soap compounds were significantly less toxic and demonstrated higher viability than SLS after a 48 h culture and a 5 min exposure. The half-maximal inhibitory concentration (IC50) obtained from the viability assay revealed values of 7.82 mM for potassium laurate (C12K), 7.56 mM for potassium oleate (C18:1K), and 0.604 mM for SLS. Therefore, natural soap appears to be valuable due to its lower toxicity, greater biodegradability in aquatic environments, enhanced safety for human cells, and potential efficiency in clinical applications.